Síntese e análise estrutural de complexos de urânio(VI) com hidrazonas, semicarbazonas e ligantes relacionados - Gatto, Claudia Cristina (2006)
Uranyl complexes with ligands with oxygen and nitrogen donors have been extensively reviewed and they have aroused interest on account of their high stability, usefulness in selective chemical separations and their formation in higher coordination numbers, but quite a few complexes of hydrazone and semicarbazone ligands have been reported. This fact was the inspiration to the search of the synthesis and characterization of new uranium complexes with hydrazones, semicarbazones and related ligands in intention to explore the reactivity and coordination behavior of the uranium, as well to understand the interactions between the metal center with these ligands. The structural study in the solid state for the characterization of the interactions in the crystalline structures of the uranium compounds synthesized was carried out with single crystal X-ray diffraction. In this way, the relation between crystalline structure and supramolecular organization could be better understood. It was characterized with single crystal X-ray diffraction 2 hydrazones and also 19 new uranium complexes. Many metallic complexes had been found as monomers, dimers, trimers and until tetramer, what it demonstrates the versatility and the geometry of coordination of the uranium atom and the ligands used in the formation of these complexes. The hydrogen bonds also play an important role in the crystallization and stabilization of the three-dimensional structures. There are intra and intermoleculares interactions between ligands molecules, solvent group and uranyl oxo ligands, however the hydrogen-bonding interactions have no influence in the coordination of the metal atom. The uranium atoms in the complexes present high coordination numbers and a polyhedron of coordination as a pentagonal bipyramid and/or hexagonal bipyramid.